ТЕРАПЕВТИЧЕСКИЕ ОБЩЕСТВА СЕВЕРО-КАВКАЗСКОГО ФЕДЕРАЛЬНОГО ОКРУГА - А. В. Ягода (SINAPS LLC, 2012)
In the North Caucasus Federal District operate seven scientific medical societies of physicians as an autonomous. Societies have a different history and experience. Thus, the association of therapists in Dagestan, North Ossetia and the Stavropol region exist during many decades. In other regions of the Northern Caucasus societies are relatively young due to the peculiarities of formation of the federal entities. Almost all regions have on their territory higher medical educational institutions - academies and medical faculties of universities, providing a scientific, methodological framework and a high level of clinical therapeutic services.